From Policy to Quality: The Director's Strategy in Enhancing Service Quality at Islamic Boarding School - Raden Muhammad Syahrial; Sya'roni; Musli (Jawda: Journal of Islamic Education Management, 2025)
The rapid growth of educational institutions, particularly Islamic boarding schools (pesantren), requires effective management strategies to improve service quality. Nevertheless, few studies have examined the director’s strategic role in managing facilities and infrastructure to enhance pesantren services, considering the unique complexities of this educational context.. This qualitative study investigates how the director of Pondok Karya Pembangunan (PKP) Al-Hidayah in Jambi Province formulates, implements, and evaluates strategies for service quality improvement, with a particular focus on developing the facilities and infrastructure of pesantren. Data were collected through in-depth interviews, direct observation, and internal documentation analysis. Findings indicate that the director employs a comprehensive strategic approach. Planning involves internal/external analysis, strategy selection, and policy formulation for facility quality. Implementation utilizes a holistic method through a dedicated coordinator, diversified funding, external collaborations, proactive maintenance, enhanced human resource capacity, and master plan development. Evaluation is conducted via a supervision program (observations/reports), routine meetings, and periodic physical audits. This research highlights effective leadership and management practices crucial for ensuring service quality in religious educational institutions amidst dynamic changes.